Associations of Occupational Stressors, Perceived Organizational Support, and Psychological Capital with Work Engagement among Chinese Female Nurses. (12th January 2017) - Wang, Xiaoxi; Liu, Li; Zou, Futing; Hao, Junhui; Wu, Hui
Abstract : This study aimed to explore the associations of occupational stressors (extrinsic effort, reward, and overcommitment), perceived organizational support (POS), and psychological capital (PsyCap) and its components (self-efficacy, hope, resilience, and optimism) with work engagement and the mediating roles of PsyCap and its components among Chinese female nurses within the framework of the job demands-resources (JD-R) model. A cross-sectional sample (1, 330) completed the Utrecht Work Engagement Scale, Effort-Reward Imbalance Scale, Survey of POS, and PsyCap Questionnaire, and effective respondents were 1, 016 (76.4%). Hierarchical regression analysis and Preacher and Hayes' asymptotic and resampling strategies were used. Extrinsic effort was negatively associated with vigor, dedication, and absorption, while POS, PsyCap, and hope were positively associated with them. Reward and overcommitment were positively associated with dedication and absorption. Optimism was positively associated with vigor and dedication. Optimism mediated the associations of extrinsic effort, reward, and POS with vigor and dedication. PsyCap and hope mediated the associations of POS with vigor, dedication, and absorption. There is a low level of work engagement among Chinese female nurses. Extrinsic effort could reduce work engagement, while reward, overcommitment, POS, PsyCap, hope, and optimism could enhance work engagement. Hospital managers should develop the PsyCap of female nurses through controlling occupational stressors and establishing supportive organizational climate to enhance their work engagement.